Changes in the density of human resources in health during the COVID-19 epidemic in Peru, april - august 2020 - Murillo-Peña, Juan Pablo (2021)
Objective. To analyze the changes in the density of human resources in health (DHRH), in the Ministry of Health at the regional and provincial level in Peru, in order to describe the response of the health system on this component during the COVID-19 epidemic. Methods. Descriptivestudy based on the analysis of the INFORHUS national database of the Ministry of Health. To calculate the DHRH, the health personnel registered in the INFORHUS database were considered as the numerator and the population assigned to the Seguro Integral de Salud - SIS as the denominator. Health personnel who died and were still registered, and personnel diagnosed with COVID-19 by rapid or molecular testing during the months considered in the analysis, were excluded. The percentage changes of DHRH between the months of april to august 2020 were analyzed at the regional and provincial level in Peru. Results. In the april-august 2020 period, in response to the first phase of the COVID-19 pandemic, Peru increased the DHRH by 5,1%. At the regional level, this increase was achieved in 15 of the 25 regions with a variation from 0,2% to 12,3%, and a sharp and sustained reduction in appointed personnel was observed, together with an increase in personnel with temporary contracts. In the rest of the regions, a reduction in DHRH was observed, which ranged from -0,7% to -7,7%. Conclusions. DHRH in Peru showed a slight increase at the national level during the first quarantine period due to the COVID-19 pandemic, however, this result has not been equitable in the different regions and provinces at the national level. This suggests a limitation in the scope of the measures taken by the government, and the need to take actions to strengthen the health situation and deployment of human resources in health in the most disadvantaged sectors.